SO2 AND HCHO OVER THE MAJOR CITIES OF KAZAKHSTAN FROM 2005 TO 2016: INFLUENCE OF POLITICAL, ECONOMIC AND INDUSTRIAL CHANGES - Darynova, Zhuldyz; Amouei Torkmahalleh, Mehdi; Abdrakhmanov, Talgat; Sabyrzhan, Serik; Sagynov, Sultan; Hopke, Philip K.; Kushta, Jonilda (Nature Research, 2020)
Satellite observations of the Ozone Monitoring Instrument (OMI) for tropospheric sulfur dioxide (SO2) and formaldehyde (HCHO) column mass densities (CMD) are analyzed for the period 2005–2016 over the atmosphere of Kazakhstan. Regarding SO2 the major hot spots relate to regions with high population and large industrial facilities. Such an example is the city of Ekibastuz that hosts the biggest thermal power plants in the country and exhibits the higher SO2 CMD at national level. The annual average CMD in Ekibastuz reaches 2.5 × 10−5 kg/m2, whereas for the rest of the country respective values are 6 times lower. Other hotspots, mostly urban conglomerates such as Almaty and Nur-Sultan, experience high CMDs of SO2 in particular years, such as 2008. One of the main reasons for this behavior is the financial crisis of 2008, forcing the application of alternate heating sources based on cheap low-quality coal. Regarding HCHO, an oxygenated Volatile Organic Compound (VOC), the main hot spot is noticed over the city Atyrau, the oil capital of the country where two massive oil fields are located. The highest HCHO CMD (9 × 1015 molecules/cm2) appears in the summertime due to secondary production as a result of the photo-oxidation of VOCs emitted by industrial sectors, oil refinery plants and vehicles. Strongly elevated HCHO amounts are also observed in Nur-Sultan in 2012 that could be due to the residential coal combustion and vehicle exhaust under poor winter dispersion conditions. Significant reductions in HCHO observed between 2012 and 2015 can be attributed to two significant measures implemented in the country in 2013 that aimed at the improvement of air quality: the introduction of the emission trading system (ETS) for greenhouse gases and Euro-4 standards for new vehicles entering the national vehicle fleet.
Keywords: Research Subject Categories::TECHNOLOGY